Trends in Growth and Labor Markets in the Last Two Decades: Evidence from Tunisia - Deeksha Kokas; Abdel Rahman El Lahga; Gladys López-Acevedo (Institute of Labor Economics (IZA), 2021)
Tunisia's GDP contracted by -8.8 percent in 2020, the worst performance since gaining independence in 1956. The poverty rate in Tunisia could reach at least 20.9, the same level recorded in 2010, and as high as 25 percent according to various estimates (Kokas et al., 2020); while inequality could reach an unprecedented Gini level of 0.41. While Tunisia has faced difficult political, economic and social challenges—in addition to the global COVID-19 pandemic—Tunisia's performance was below peer countries even during periods of strong growth. All economic sectors in Tunisia have declined, except agriculture, and structural transformation has been weak. Nearly 68 percent of workers are employed in sectors with the lowest productivity. Youth and women have been especially left behind as job growth has not kept pace with university graduates and growth in the working-age population: early 32 percent of Tunisian youth were "Not in Education, Employment, or Training" (NEET), and female labor force participation (FLFP) of 29 percent remains among the lowest in the world. Clearly, key labor market challenges in terms of poor job creation, and low quality of job have not seen much progress since the Arab Revolution. This paper aims to shed light on the main obstacles to creating sufficient employment and addressing labor market distortions in Tunisia, based on several data sources, including latest rounds of labor force surveys, and helps recognize issues that require immediate policy attention in the labor market in Tunisia.
Keywords: J31; F16; 330; labor markets; employment; Tunisia